Diffusion of Technological Innovation in Non-Formal Education: The Mediating Role of Digital Social Interaction - Ali Muchasan; Dwi Marlina Lusianti; Salim Ashar; Dhuhaa Rohmawan; Nurhuda Nurhuda (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2026)
This study examines the strategic diffusion of technological innovation in a non-formal language course institution through the lens of Diffusion of Innovation theory. While digital transformation has significantly influenced educational practices, empirical research on how technological innovation is diffused and sustained within community-based non-formal institutions remains limited. Using a qualitative case study design, data were collected through semi-structured interviews, observations, and document analysis involving 18 participants, consisting of 8 tutors and 10 learners actively engaged in technology-supported learning in Kampung Inggris, Pare. The findings reveal that innovation adoption was primarily influenced by perceived instructional relevance, ease of use, and compatibility with learning needs. Diffusion occurred through hybrid communication networks that combined interpersonal interaction with digitally mediated platforms, where early adopters served as internal change agents who modeled and legitimized technology use. Institutional support, including digital training and infrastructure, facilitated sustainability, though disparities in digital literacy hindered uniform integration. The study highlights the mediating role of digital social interaction in structuring innovation diffusion within non-formal education. By situating diffusion processes within relational and networked learning ecosystems, this research refines the contextual application of Diffusion of Innovation theory. It provides practical insights for sustaining inclusive technological transformation beyond formal educational systems.